Intellectual Origins of Islamic Resurgence in the Modern Arab World: Ibrahim M. Abu-Rabi‘. SUNY Series in Near Eastern Studies. Albany, NY: State University of New York Press, 1996, xii + 370 pp. (American Journal of Islam and Society, 1996)
Most studies of Islamist resurgence have focused on specific aspects ofthe Islamist political agenda and have sought to identify their intellectualroots in the writings of thinkers from the medieval period of Islamic history.Influenced by Iran’s Islamic revolution, these authors have been concernedprimarily with political Islam. It is rare to find a book that seeks to establishmodem Islamist thought within the context of western critical theoryand indigenous political conditions, or that explains its ideas in light of aconflict between revolutionary discourse and state hegemony. Abu-Rabi”sbook is thus all the more welcome, as it establishes a basis for considerationof Islamist thinkers that will be an essential reference in the fbtwx.The subject of this book is the thought of Sayyid Qqtb, consideredwithin the parameters of Islamic modernism, westernization, orientalism,and the contemporary Islamist response to these factors. Abu-Rabi‘ says heis undertaking an intellectual history of his subject, that of “a popular religiousmovement . . . founded by lay Muslim intellectuals” often at oddswith the traditional political and religious elites. But he considers this questionin light of the “question of continuity and discontinuity in modem Arabthought.” Influenced by Foucault, he argues that the question of epistemologicalacts and thresholds, of conceptual ruptures in the development ofideas, must be countered by the reality of continuities in Islamic thought,by the fact of an ongoing Islamic discourse whose exposition may changeaccording to historical circumstances but whose essence and focus of concernremain constant (pp. 5-6).The idea of continuity and discontinuity is a valuable method for consideringvarious themes in Arab thought, ranging from the liberal thinkersof the nuhdah (renaissance) to both secular and religious Arab responses tothe challenge of colonization and the question of how best could Arab-Islamic societies survive foreign occupation. Essential here is the questionof Arab Muslim “decline,” how and why it occurred, and how this declinemay be reversed. Abu-Rabi‘ surveys a variety of Muslim thinkers to positthree approaches to the relevance of Islamic tradition to the resolution ofthe problem of decline: the rejection of tradition in favor of intellectualstimulus from the West; a conservative approach calling for the “revival of ...